Banking law and practice in Nigeria : the core elements of banking business - Oche, Patrick N. (Jos, Nigeria: Heirs Great Commision, 2004)
The book dwells principally on the constituting element of banking law. It articulates and subjects same to in-depth analysis and presents banking law in a unique manner which invariably facilitates its comprehension.
Includes Index
lje 03/08/2013, ijb 19/03/2019
Loans
Keywords: Banking Law; Banking business